Faktor-faktor yang mempengaruhi minat mahasiswa bekerja di lembaga keuangan syariah - Cynthia Candraning; Rifqi Muhammad (Jurnal Ekonomi & Keuangan Islam, 2017)
AbstractDemand for sharia resources in various Islamic financial institutions is increasing. The rapid development of the Islamic finance industry is one of the causes. In addition, human resources that have the ability and knowledge about sharia transaction is not sufficient. This study aims to determine what factors affect the interest of students majoring in accounting to work in sharia financial institutions. Variables used include interest as an independent variable, as well as independent variables consisting of work considerations, financial rewards, work environment and spiritual. The test results show that market considerations, financial rewards/salary, work environment and spiritual have a significant influence on the interest of students working in sharia financial institutions.